Retracted Article (Medical Forum Monthly, 2023)
Article Titled “Effects of Depression Screening on Quality of Life After Diagnosis of Acute Coronary Syndrome, Single Center Experience” published with Authors (1. Abukakr Ali Saad 2. Munir Ahmed Rashid 3. Saima Dastgeer 4. Zahid Iqbal 5. Muhammad Hassan Raza 6. Imran Javed) published in Medical Forum Monthly Lahore, Med. Forum, Vol. 33, No.6 June, 2022 at pages 97-101 is hereby RETRACTED on the basis of plagiarized study.